Working with a women’s group in Titilaka, Peru to form a knitting association – an example of value based groupwork - Boeck, Thilo; Fleming, Jennie (Groupwork, 2019)
This paper discusses in detail just one group meeting utilizing the social action group work approach for a group of women in Peru wishing to establish themselves as a knitting association.  We describe the context of the work and the different elements and challenges when facilitating the workshop.  The meeting was part of a community development process supported by an NGO Amantani and a local hotel – Hotel Titilaka.  The facilitators of the session – Author 1 and Author 2 - are both Europeans